Liouville-Gelfand Type Problems for the N-Laplacian on Bounded Domains of ℝN - Silva, Elves A. B. de; Scares, Sergio H. M. [UNESP] (My University, 1999)
In this article it is used minimax methods to establish some results of existence and multiplicity of solutions for the A N-Laplacian equation on bounded domains of ℝN, with Dirichlet boundary conditions, when the nonlinearity has exponential growth. The subcriticai and critical cases are considered.